COMPARATIVE EFFECTIVENESS OF NON-PHARMACOLOGICAL INTERVENTIONS FOR DIABETIC NEUROPATHIC PAIN: A NETWORK META-ANALYSIS OF PAIN INTENSITY AND NEUROPATHIC SYMPTOM OUTCOMES - Aqila, Hammadah; Masykur, Umar Jundullah; Janet, Karensa Abby; Sulistomo, Hikmawan Wahyu; Kurniawan, Shahdevi Nandar (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Diabetic peripheral neuropathy (DPN) is a common complication of diabetes mellitus and a major cause of chronic neuropathic pain, leading to reduced quality of life. Owing to the limited efficacy and tolerability of pharmacological treatments, non-pharmacological interventions have emerged as important alternative or adjunctive options. Objective: This study aimed to compare and rank the effectiveness of non-pharmacological interventions for neuropathic pain management in patients with DPN using a network meta-analysis (NMA). Methods: This systematic review and network meta-analysis was prospectively registered in PROSPERO (CRD420261295534). A systematic literature search was conducted in PubMed, Springer Nature, the Cochrane Library, and Taylor & Francis from inception to May 30, 2025. Randomized controlled trials evaluating non-pharmacological interventions for DPN-related neuropathic pain were included. Pain intensity and neuropathic pain symptom scores were analyzed using a frequentist random-effects NMA. Treatment effects were expressed as standardized mean differences (SMDs) with 95% confidence intervals (CIs), and intervention rankings were estimated using the surface under the cumulative ranking curve (SUCRA). Results: Forty-seven RCTs involving 3,354 participants and 10 intervention categories were included. For pain intensity, invasive neuromodulation demonstrated the greatest reduction compared with control (SMD = –5.94; 95% CI –7.78 to –4.11) and ranked highest (SUCRA = 0.97). Acupuncture-based therapies and manual/massage therapies also showed notable effects. For neuropathic pain symptom scores, invasive neuromodulation again ranked highest (SMD = –3.20; 95% CI –5.96 to –0.43; SUCRA = 0.74), followed by acupuncture-based and electromagnetic field therapies. Sensitivity analyses confirmed the robustness of the findings, although potential publication bias was detected for pain intensity outcomes. Conclusion: This NMA provides a comprehensive comparative ranking of non-pharmacological interventions for neuropathic pain in DPN, highlighting invasive neuromodulation as the most effective modality and supporting the role of selected non-pharmacological therapies in clinical practice.